Religion and World Politics: Connecting Theory with Practice - Wilson, Erin K. (Taylor & Francis, 2023)
Religion and World Politics provides a short, accessible, and practical introduction to how we can understand the place of religion in world politics in a more comprehensive, contextually relevant way. Is religion central or irrelevant, positive or negative in world politics today? So much political commentary and analysis focuses on these issues. But these are the wrong questions to be asking. Designed for practitioners, policymakers, and newcomers to the topic of religion and global politics, this book emphasises that religion is not something clear, identifiable, and definable, but is fluid and shifting. Consequently, we need analytical frameworks that help us to make sense of this ever-changing phenomenon. The authorpresents a critical, intersectional framework for analysing religion and applies this to case studies of three core areas of international relations (IR) analysis: (1) conflict, violence, and security; (2) development and humanitarianism; and (3) human rights, law, and public life. These cases highlight how assumptions about what religion is and does affect policymakers, theorists, and activists. The book demonstrates the damage that has been done through policies and programmes based on unquestioned assumptions and the possibilities and insights to be gained by incorporating the critical study of religion into research, policymaking, and practice. This book will be of great interest to students of global politics, IR, religion, and security studies, as well as diplomats, civil servants, policymakers, journalists, and civil society practitioners. It will also benefit IR scholars interested in developing their research to include religion, as well as scholars of religion from disciplines outside IR interested in a deeper understanding of religion and world politics